2022
DOI: 10.5747/ca.2022.v18.n1.a479
|View full text |Cite
|
Sign up to set email alerts
|

Root and shoot development of corn seedlings as affected by rhizobacteria

Abstract: Multifunctional microorganisms are beneficial microorganisms able of promoting plant growth through direct and indirect mechanisms. Because of this, has enormous potential for use when aiming a sustainable agriculture. The objective of this work was to determine the effect of seed inoculation with multifunctional microorganisms on the initial development of corn seedlings. The experiment was carried out under controlled conditions in a completely randomized design, with seven treatments and six replications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Figure 2 displays images of the root system of soybean seedlings treated with the beneficial rhizobacteria evaluated in this study. Similar results were obtained for the root system of rice and corn treated with Azospirillum sp., showing an increase of 86.3% and 43.7%, respectively (Fernandes et al, 2021;Cruz et al, 2022) Serratia marcescens (BRM 32114), and Bacillus spp. (BRM63573) showed a significant increase in total dry matter (MST) of 36.6%, 35.9%, and 32.4%, respectively, and in aboveground dry matter (MSPA) by 39.0%, 43.8%, and 41.0%, respectively, compared to the control treatment (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 displays images of the root system of soybean seedlings treated with the beneficial rhizobacteria evaluated in this study. Similar results were obtained for the root system of rice and corn treated with Azospirillum sp., showing an increase of 86.3% and 43.7%, respectively (Fernandes et al, 2021;Cruz et al, 2022) Serratia marcescens (BRM 32114), and Bacillus spp. (BRM63573) showed a significant increase in total dry matter (MST) of 36.6%, 35.9%, and 32.4%, respectively, and in aboveground dry matter (MSPA) by 39.0%, 43.8%, and 41.0%, respectively, compared to the control treatment (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…They contribute to biological nitrogen fixation (Pacentchuck et al, 2020), inorganic phosphate solubilization, and organic phosphate mineralization, as well as inhibition of ethylene production (Santoyo et al, 2016), and mitigation of oxidative, saline, and water stresses. Recent studies have demonstrated the beneficial effects of multifunctional microorganisms in crops such as rice (Fernandes et al, 2021), maize (Cruz et al, 2022), common beans (Rezende et al, 2021), soybeans (Chagas et al, 2022), among others. For soybean seed microbiolization, the seeds were immersed in bacterial suspensions (Filippi et al, 2011) produced by cultivating the mentioned rhizobacteria on solid medium (nutrient agar).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. da Silva & Dourado, 2022a). These mechanisms mainly benefit the greater root development, providing conditions for the plant to explore a larger volume of soil and absorb more water and nutrients (Cruz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%